Planning Conservation Strategies of Guiana Dolphin Related to Canal Flow and Habitat Changes in the Estuarine Lagunar Complex of Cananéia - Godoy, Daniela Ferro de; Pavanato, Heloise; Andriolo, Artur (Frontiers in Conservation Science, 2022)
Anthropogenic activities have altered the structure and function of coastal and estuarine ecosystems, affecting the animals that occur in these areas. Predictive models are useful to evaluate the impact of anthropogenic characteristics over species distribution. In this study, we used generalized linear models to assess the influence Valo Grande canal, which allows fresh water to enter the Estuarine Lagunar Complex of Cananéia, has on the occurrence of Guiana dolphins. A population of this species resides in the study area, which comprises many coastal and marine protected areas. Abiotic data and information on species occurrence were gathered between January 2012 and November 2014, during three fieldworks per season, covering four sectors within the estuary. The predictions resulting from generalized linear models indicated that the discharge of fresh water, which decreases salinity in the estuary, has a negative influence on the populations of dolphins in all sectors but, mainly, on sector IV, the closest to Valo Grande Canal. Thus, it is clear that Guiana dolphins presented a heterogeneous distribution within the studied estuary, and the areas of higher concentration of individuals deserve greater attention during the elaboration of conservation strategies.